2021
DOI: 10.1038/s41598-021-81815-2
|View full text |Cite
|
Sign up to set email alerts
|

Sulforaphane induces S-phase arrest and apoptosis via p53-dependent manner in gastric cancer cells

Abstract: Sulforaphane (SFN) extracted from broccoli sprout has previously been investigated for its potential properties in cancers, however, the underlying mechanisms of the anticancer activity of SFN remain not fully understood. In the present study, we investigate the effects of SFN on cell proliferation, cell cycle, cell apoptosis, and also the expression of several cell cycle and apoptosis-related genes by MTT assay, flow cytometry and western blot analysis in gastric cancer (GC) cells. The results showed that SFN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 65 publications
1
44
0
Order By: Relevance
“…In cancer cells, cyclic abnormalities and anti-apoptosis effects are common, and the capacity to induce cell cycle arrest and enhance apoptosis is a consideration in choosing potential chemotherapeutic agents [56,57]. The results of our study showed that SFN induced S-phase arrest and decreased invasion in U87MG and U373MG cells, which was consistent with previous reports by Wang et al that SFN provokes S-phase arrest via p53-dependent antiproliferation and apoptosis induction in gastric cancer cells [19]. One of the most common abnormalities in gliomas is mutations in the p53 (also known as TP53) gene.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In cancer cells, cyclic abnormalities and anti-apoptosis effects are common, and the capacity to induce cell cycle arrest and enhance apoptosis is a consideration in choosing potential chemotherapeutic agents [56,57]. The results of our study showed that SFN induced S-phase arrest and decreased invasion in U87MG and U373MG cells, which was consistent with previous reports by Wang et al that SFN provokes S-phase arrest via p53-dependent antiproliferation and apoptosis induction in gastric cancer cells [19]. One of the most common abnormalities in gliomas is mutations in the p53 (also known as TP53) gene.…”
Section: Discussionsupporting
confidence: 92%
“…Prompted by the above findings, we examined whether SFN influenced the cell cycle of GBM cells. SFN has been implicated in the regulation of cell proliferation in human cancer cells in several research studies [19,29]. The GBM cells were treated with 20, 40 and 80 µΜ of SFN for 48 h under hypoxic or normoxic conditions.…”
Section: The Effects Of Sfn On Cell Cycle and Cell Motilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Sulforaphane treatment also led to suppression of key colorectal cancer stem cell markers, such as CD44 and CD133 in HCT116 and SW480 spheroids, facilitated by the TAp63α/Lgr5/β-catenin pathway (Chen et al, 2020), suggesting that exposure to sulforaphane could lead to lowered cell proliferation activity. On the contrary, sulforaphane treatment (<10 µM) led to increased cell proliferation and also lowered expression of key apoptotic proteins Bcl-2 and Bax, but concentrations of greater than 10 µM caused cell death in p53-wild-type HCT116 cells (Wang et al, 2021). There are few animal or human studies that have assessed the role of sulforaphane on colon cancer.…”
Section: Colon Cancermentioning
confidence: 99%
“…The expression level of p21, which directly regulated the S‐phase transition was detected by WB, and exhibited an increasing trend in a dose‐dependent manner. The results above indicated that the DM‐BBR effectively inhibited cell proliferation via inducing cell cycle arrest at S phase partly by regulating the expression of cell cycle‐related genes in HCT‐116 cells 20 (Figure 5A‐C). In addition, the expression of cyclin P27 was significantly increased, indicating that DM‐BBR affects the normal progress of the cell cycle and also inhibited the proliferation in HCT‐116 cell line (Figure 5C).…”
Section: Resultsmentioning
confidence: 87%